Preferred parenting style in rural community and its association with socio-demographic variables: a cross sectional study - Somashekar, Malenahally Puttannaiah; Chandrashekarappa, Smitha Malenahalli; Chandana, Hombaiah (International Journal Of Community Medicine And Public Health, 2019)
Background: Parenting styles are the methods used by parents when dealing with their children. Some theorists in counseling and psychotherapy have shown the importance of parenting styles in forming children personalities. Baumrind recommended three prototypes of parenting styles: authoritative, authoritarian, and permissive. Parenting styles are associated with different levels of social and cognitive competence in children and adolescents. Hence with this background the following study was undertaken to understand the preferred parenting style practiced in the rural community of southern part of India. The objective of this study is to assess the parenting style practiced in the rural community and to assess the association of socio-demographic variables with the type of parenting styles practiced in rural community. Methods: It is a cross-sectional study, conducted in Basavanapura village of Hunasuru taluk of Mysuru district. 141 parents were selected by simple random sampling. Data was collected using parenting style questionnaire (PSQ). The questionnaire also included information on socio demographic variables. Data was analyzed using SPSS V.24. Analysis is done using descriptive statistics like percentage and inferential statistics like chi square analysis to find the association between socio demographic variables and preferred parenting styles. Results: The most preferred parenting style reported was authoritative (63.2%) followed by authoritarian (26.2%) and permissive (10.6%) types. Years of marriage was found to be significantly associated with preferred parenting styles. Conclusions: Nearly three fourth of the parents practiced authoritative parenting style with this type of parenting style adopted by parents having children less than twenty years.